Husserl Reading Kant. Remarks on Reason and its Limits - Rizo-Patrón, Rosemary (2012)
A preliminary overview of Husserl reading Kant shows that both thinkers represent two essentially different types of philosophies in their methods and reach. The judgement made by Husserl about Kant allows to state that we are facing two different privileged intuitions. Nevertheless, it also allows to state a “family resemblance”–if not in their styles and methodology– in certain ground convictions regarding philosophy and reason’s finite nature. This paper approaches, from a Husserlian perspective, the relationship between “experience and judgment” –proper to a “Transcendental Theory of Elements”– and in that between “science and philosophy” –corresponding to a “Transcendental Theory of Method”. Furthermore, it will approach the distinction between natural and transcendental-phenomenological attitudes that allow Husserl to introduce two levels of philosophical interrogation and two types of philosophical anthropologies, corresponding to the splitting of the ego – a pure constitutive ego and a constituted one. This last will lead to the genetic problem of the ego’s self-constitution from the deepest strata of passive instinctive life (unconscious and irrational) towards rational life in a teleological ascending movement that enacts the Kantian problem of reason’s finitude. Despite of the incorporation that Husserl makes of a teleology of Leibnizian type that resolves the Kantian hiatus between sensible and intelligible world, the Kant connoisseurs will recognize his tracks in the configuration of the Husserlian trascendental phenomenology.